Investigating attention‐deficit hyperactivity disorder and autism spectrum disorder traits in the general population: What happens in adult life?. (14th July 2020) - Riglin, Lucy; Leppert, Beate; Langley, Kate; Thapar, Ajay K.; O'Donovan, Michael C.; Davey Smith, George; Stergiakouli, Evie; Tilling, Kate; Thapar, Anita
Abstract : Background: Attention‐deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) are generally considered early‐onset disorders so most research has therefore tended to focus on children. Differences between ADHD/ASD in adult life and childhood have been noted, but few population‐based studies have examined them in adulthood. Furthermore, the interpretation of findings is hampered by changes in measure and from parent report to self‐report. Method: We examined continuous/trait measures of parent‐ and self‐rated ADHD and ASD in adulthood (age 25 years) in a UK prospective longitudinal sample ALPSAC (the Avon Longitudinal Study of Parents and Children), using many of the same measures that parents reported on in childhood ( N = 6, 064). Our aim was to investigate these traits in this population for mean‐level sex differences, overlaps with other cognitive, learning and communication problems and their associations with polygenic risk scores (PRS) for neuropsychiatric disorders (ADHD, ASD, schizophrenia, depression and anxiety). Results: ADHD and ASD traits in adulthood, as in childhood, showed associations with childhood cognitive, learning and communication problems and adult communication/language measures, although less so for self‐ratings than parent‐ratings. Males had higher ADHD and ASD trait levels, but this was not as marked as in childhood. In adulthood, ADHD (both parent‐ and self‐rated) and ASD (parent‐rated) symptoms showed associations with ADHD PRS; self‐reported ADHD also showed association with depression PRS, whereas self‐reported ASD did not show strong PRS associations. Conclusions: Our findings suggest that in young adults, ADHD and ASD symptoms have similar characteristics as they do in childhood. Associations with other cognitive, learning and communication problems, and ADHD PRS were somewhat less pronounced for self‐reported adult ADHD and ASD symptoms, suggesting that even at age 25, parent reports, where available, could be clinically useful.